Homological stabilization for dedekind rings of the arithmetic type - Zainalov, B. R.; Suslin, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study the problem of stabilization in the higher K -theory of rings and improved stabilization. The triviality of the group of standard cycles is established in the case of arithmetic-type rings. Some applications of the obtained results to the problem of homological stabilization are presented.